SQUAB—I: The First Release of Strange QUasar Candidates With ABnormal Astrometric Characteristics From Gaia EDR3 and SDSS - Wu, Qi-Qi; Liao, Shi-Long; Ji, Xiang; Qi, Zhao-Xiang; Zheng, Zhen-Ya; Lin, Ru-Qiu; Zhang, Ying-Kang; An, Tao (Frontiers in Astronomy and Space Sciences, 2022)
Given their extremely large distances and small apparent sizes, quasars are generally considered as objects with near-zero parallax and proper motion . However, some special quasars may behave abnormally, such as quasar pairs, lensed quasars, AGNs with bright parsec-scale optical jets, which are scientifically interesting objects, such as binary black holes. These quasars may come with astrometric jitter detectable with Gaia data, or significant changes in the position at different wavelengths. In this work, we aim to find these quasar candidates from Gaia EDR3 astrometric data combining with Sloan Digital Sky Survey (SDSS) spectroscopic data to provide a candidate catalog to the science community. We propose a series of criteria for selecting abnormal quasars based on Gaia astrometric data. We obtain two catalogs containing 157 sources and 55 sources, respectively. We demonstrate that these sources are not suitable for establishing the reference frame, and they are potential candidates of quasar pairs.